Performance assessment of artificial neural networks and support vector regression models for stream flow predictions - Ateeq-ur-Rauf; Abdul Razzaq Ghumman; Sajjad Ahmad; Hashim Nisar Hashmi (Environmental Monitoring and Assessment, 2018)

Developing nonlinear models for sediment load estimation in an irrigation canal - Fahad Ahmed; Muhammad Hassan; Hashim Nisar Hashmi (Acta Geophysica, 2018)

Experimental and numerical investigations for optimal emitter spacing in drip irrigation - Abdul Razzaq Ghumman; Muhammad Iqbal; Sajjad Ahmed; Hashim Nisar Hashmi (Irrigation and Drainage, 2018)
With the goal of determining optimal emitter spacing in drip irrigation, experiments were performed to examine the effects of emitter discharge on the wetted perimeter and spacing of emitters. Four types of soils were investigated using emitter discharge of 1.0, 2.0, 3.0 and 4.0 l h −1 . Wetting diameter was measured at six equal time intervals of water application. An equal volume of water was applied. After 1 h of supply of water, wetted soil was cut to observe the maximum wetted width and depth. Wet soil samples were taken from every patch of 10 × 10 cm to find the percentage of moisture by the gravimetric method. Empirical equations were developed for wetted depth and radius. Additional experiments with emitter discharge of 1–18 l h −1 were performed in sandy loam to obtain more data for accurate estimation of the coefficients of the empirical equations. Two computer programs based on trial and error and the generalized reduced‐gradient non‐linear‐optimized technique were used to find values of the coefficients. Root mean square error between the measured and simulated wetted radius and depth was minimized in optimization. Optimal emitter spacing for each type of soil was determined from the recorded data, which was found to be 35, 40, 40 and 45 cm in sandy loam, loam, clayey loam and clay respectively. © 2018 John Wiley & Sons, Ltd.

Performance evaluation of 1-D numerical model HEC-RAS towards modeling sediment depositions and sediment flushing operations for the reservoirs - Habib-ur-Rehman; Muhammad Asif Chaudhry; Usman Ali Naeem; Hashim Nisar Hashmi (Environmental Monitoring and Assessment, 2018)

Possible options to slow down the advancement rate of Tarbela delta - Habib-ur-Rehman; Mirza Abdul Rehman; Usman Ali Naeem; Hashim Nisar Hashmi; Abdul Sattar Shakir (Environmental Monitoring and Assessment, 2018)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Performance assessment of aquatic macrophytes for treatment of municipal wastewater - Mumtaz Shah; Hashim Nisar Hashmi; Arshad Ali; Abdul Razzaq Ghumman (Journal of Environmental Health Science and Engineering, 2014)

Development of geomorphologic instantaneous unit hydrograph for a large watershed - Abdul Razzaq Ghumman; Muhammad Masood Ahmad; Hashim Nisar Hashmi; Mumtaz Ahmad Kamal (Environmental Monitoring and Assessment, 2012)

Environmental and socio-economic impacts of pipe drainage in Pakistan - Abdul Razzaq Ghumman; Yousry Mahmoud Ghazaw; Hashim Nisar Hashmi; Mumtaz Ahmed Kamal; Muhammed Farooq Niazi (Environmental Monitoring and Assessment, 2012)

Estimation of a Unique Pair of Nash Model Parameters: An Optimization Approach - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad; Hashim Nisar Hashmi (Water Resources Management, 2010)